2017
DOI: 10.1016/j.tox.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate and Roundup® alter morphology and behavior in zebrafish

Abstract: Glyphosate has become the most widely used herbicide in the world, due to the wide scale adoption of transgenic glyphosate resistant crops after its introduction in 1996. Glyphosate may be used alone, but it is commonly applied as an active ingredient of the herbicide Roundup. This pesticide contains several adjuvants, which may promote an unknown toxicity. The indiscriminate application poses numerous problems, both for the health of the applicators and consumers, and for the environment, contaminating the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 47 publications
3
53
2
6
Order By: Relevance
“…Effects of glyphosate on somatic and ovarian growth, as well as of glyphosatebased formulations on ovarian growth and immune status of freshwater and estuarine crab species were reported (Hong et al, 2017;Avigliano et al, 2018;Canosa et al, 2018). Toxicities have extensively been reported for fish, including the zebrafish D. rerio, on which both glyphosate (Armiliato et al, 2014;Lopes et al, 2014;Uren Webster et al, 2014) and its formulated products (Bridi et al, 2017;Sulukan et al, 2017) were found to exert acute toxicity through inhibited carbonic anhydrase activity due to oxidative stress (production of reactive oxygen species), cellular apoptosis, effects on locomotor activity and aversive behavior, as well as reproduction disorders, deteriorating sperm quality, embryotoxicity malformations, and other endocrine disruption symptoms. Another study found carp (Cyprinus carpio) more sensitive to embryotoxicity of glyphosate at high concentrations (50 mg/l) than zebrafish (Fiorino et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…Effects of glyphosate on somatic and ovarian growth, as well as of glyphosatebased formulations on ovarian growth and immune status of freshwater and estuarine crab species were reported (Hong et al, 2017;Avigliano et al, 2018;Canosa et al, 2018). Toxicities have extensively been reported for fish, including the zebrafish D. rerio, on which both glyphosate (Armiliato et al, 2014;Lopes et al, 2014;Uren Webster et al, 2014) and its formulated products (Bridi et al, 2017;Sulukan et al, 2017) were found to exert acute toxicity through inhibited carbonic anhydrase activity due to oxidative stress (production of reactive oxygen species), cellular apoptosis, effects on locomotor activity and aversive behavior, as well as reproduction disorders, deteriorating sperm quality, embryotoxicity malformations, and other endocrine disruption symptoms. Another study found carp (Cyprinus carpio) more sensitive to embryotoxicity of glyphosate at high concentrations (50 mg/l) than zebrafish (Fiorino et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…In published literature reports are available about the acute toxicity of glyphosate (Piola et al, 2013) but scanty information is available about its adverse effects on exposed organisms at very low concentrations. However, the toxic effects of glyphosate might be because of occurrence of sub lethal and complex changes like alteration in metabolic conditions, mitochondrial dysfunction, immunotoxicity, developmental toxicity, neurotoxicity and endocrine disruption (Bridi et al, 2017;Schimpf et al, 2017). Previously, in accessible published literature, no information is available regarding the adverse effects of glyphosate on male birds.…”
Section: Introductionmentioning
confidence: 99%
“…The most common approach when one is assessing behavioral responses related to movement is to focus on displacement patterns such as swimming activities (orientation, posture, frequency, duration, and speed of movements), spontaneous activity, burst swimming, ability to capture prey and escape from predators, etc. (Nakamura ; Little et al ; Saglio et al ; Bridges ; Zhou and Weis ; Fleeger et al ; Ren et al ; Oliveira et al ; Bridi et al ; Jutfelt et al, ). Therefore, in behavioral ecotoxicology, the response considered as avoidance is, in reality, a predictive endpoint about what would be expected to occur if, under real field conditions, organisms were mandatorily and continuously exposed to contamination (Farr et al ).…”
Section: Introductionmentioning
confidence: 99%